DETERMINATION OF THE QUALITATIVE INFLUENCE OF FACTORS ON THE SENSITIVITY OF THE CAPACITIVE HUMIDITY SENSOR OF A TWO-LAYER STRUCTURE BASED ON MULTIFACTOR DISPERSION ANALYSIS - KRYLIK, LYUDMILA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A multifactorial dispersion analysis was applied in order to qualitatively assess the influence of the following factors: thickness of the moisture-sensitive layer; the thickness of the polymer coating as a protective layer; the concentration of the NaCl salt solution as an adsorbent material and their combined effect on the sensitivity of the capacitive humidity sensor of the two-layer structure. Capacitive humidity sensors of a two-layer structure, made on a sitall substrate, served as experimental samples. The copper film, which forms the covers of the capacitive humidity sensors, is applied to the surface of the sitall substrate in the form of a meander. In the developed design, the moisture-sensitive layer is hygroscopic salt, which performs the function of a dielectric. A moisture-absorbing film of polymethylmethacrylate serves as a protective layer. A multifactorial plan is developed for the case of three qualitative factors. Using multifactorial dispersion analysis, it was proved that the response of the model, that is, the sensitivity of the capacitive humidity sensor of the two-layer structure, is influenced by such factors as the thickness of the protective layer, the concentration of the NaCl salt solution, as well as the combined effect of factors such as the thickness of the moisture-sensitive layer + the concentration of the salt solution; the thickness of the protective layer + concentration of the salt solution. That is, the difference in the response values of the model is related to the change in the value of the factor and cannot be caused only by its random nature. However, the response of the model is significantly affected by the combined effect of the factor − the thickness of the protective layer + the concentration of the salt solution. In this case, the value of Fisher's criterion, which is observed in the experiment, significantly exceeds the critical value of Fisher's criterion F >Fkr (13.01>4.49). The influence of such factors as the thickness of the moisture-sensitive layer; the thickness of the moisture-sensitive layer + the thickness of the protective layer; the thickness of the moisture-sensitive layer + the thickness of the protective layer + the concentration of the salt solution is insignificant, that is, the difference in the response values of the model is due to its random nature. Using the dispersion analysis of the influence of the factor, it was proved that the sensitivity of capacitive humidity sensors is affected not only by the concentration of the NaCl salt solution, which was used to create a moisture-sensitive layer, but also by the design of the sensor.
Keywords: multifactorial dispersion analysis; factor; model response; Fisher's criterion; sensitivity; capacitive humidity sensor